EKSISTENSI BUDAYA FALGALI DALAM KEHIDUPAN MASYARAKAT DESA BOBANE INDAH KECAMATAN PATANI BARAT KABUPATEN HALMAHERA TENGAH - Mustakim Thamrin, Dra. Fonny J. Waani, M.Si (HOLISTIK, Journal Of Social and Culture, 2015)
Falgali is a form of help please. Falgali capital is the basis of the Bobane Indah community village in doing any activity of life. Falgali used at the time of the community celebrating a marriage feast, people died, building houses and other activities associated with mutual interests. Falgali build a house in the Bobane Indah community village only done to donate power, facilities such as the house, sand, stone, gravel, cement and other material, who became the needs of the house provided by its owner. After material in prepare overall falgali the process begins. Falgali this is happening because based on the motto by Central Halmahera region namely fagogoru or known as Ngaku Rasai ( of a fraternity ), Sopan re Santun ( polite manners and mannered ), Budi re Bahasa ( mind and language ), Memoi re Mafaat ( put to shame and fear ). This knowledge on which to base in beautiful activities in the community in Bobane village. Fagogoru is a concept, the ideas that were a symbol of Central Halmahera region. In community life fagogoru has become personality of a general and become a view of life. This is what background the Bobane Indah community village falgali so that still in progress. Although falgali has become identity to unite individual by individual, the community the one with the other community. But not all the community actualization in social life, because in other subdistricts in the Central Halmahera region falgali already started to decrease so also several villages in West Patani district. However in the village of Bobane Indah falgali still executed in full in activities their lives, so our activities falgali already be entrenched in community life. Cultural activity by Koentjaraningrat ( 2002 ) can affect the mind of citizens in which the culture concerned is alive. Cultural system who live together in a society, give the soul to the community it. The system that culture not regardless between one with another, but always concerned become a system. Keywords : existence, falgali culture, social life.